“ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PENJUALAN PRODUK AIR MINERAL PADA CV. AIDRAT PACIRAN LAMONGAN - Mudakir (eBA Journal: Journal Economic, Bussines dan Accounting, 2015)
Analisis is marketing strategy in the effort increase Mineral Water product sell on CV.AIDRAT Paciran Lamongan. constitute one of effort which moves at potion sell area saji's readymineral water namely Aidrat's Mineral Water. To know how big sell step-up that did by firm.In analisis statistic analisis utilizes this research linear regression bifilaring to sees onehow far promotion factor (X1) and distribution (X2) to grocer (Y. ). Result that gotten byfollowing it wills be entry on CV. Aidrat Lamongan.Regression analysis points out that quality factor constitute factor that have sizeableinfluence to keputusa Mineral Water product sell Aidrat (Y. ) padaCV. Aidrat Lamongan.analisis's count collectively utilize quiz f acquired appreciative Fhitung as big as 14,932, thispromotion variable matter (X1), and distribution (X2) ala togethering to have positive influenceto sell (Y. ).Partially pass through quiz t one was done by writer at gets result as big as 1,743 (t1)promotion variable matter (X1) giving influence that signifikan to sell (Y. ) and variabledistribution (X2) gotten by result as big as 5,178 (t2) giving influence that signifikan to sell (Y. )Between that free variable variable distribution (X2) having the most influencedominant to buy decision (Y. )